2008
DOI: 10.1021/bc800216p
|View full text |Cite
|
Sign up to set email alerts
|

Fluorophore Labeling Enables Imaging and Evaluation of Specific CXCR4−Ligand Interaction at the Cell Membrane for Fluorescence-Based Screening

Abstract: Development of CXCR4-specific ligands is an important issue in chemotherapy of HIV infection, cancer metastasis, and rheumatoid arthritis, and numerous potential ligands have been developed to date. However, it is difficult to assess their binding mode and specificity because of uncertainties in the structure of the CXCR4-ligand complexes. To address this problem, we have synthesized fluorophore labeled Ac-TZ14011, which is derived from T140, a powerful CXCR4 antagonist. Binding of Ac-TZ14011 to CXCR4 on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 24 publications
2
58
0
Order By: Relevance
“…[8,9] For CXCR4 targeting several peptidic probes have been reported, including the cyclic Ac-TZ14011 peptide, and also a chelate-based fluorescent probe. [10][11][12][13][14][15][16] Transition-metal complexes based on, for example, iridium-(III), rhenium(I) and ruthenium(II) are attaining significant interest for application in imaging. [17][18][19][20][21][22][23][24][25][26][27][28] These phosphorescent metal complexes often posses better photophysical properties than organic fluorophores, such as long luminescence lifetimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9] For CXCR4 targeting several peptidic probes have been reported, including the cyclic Ac-TZ14011 peptide, and also a chelate-based fluorescent probe. [10][11][12][13][14][15][16] Transition-metal complexes based on, for example, iridium-(III), rhenium(I) and ruthenium(II) are attaining significant interest for application in imaging. [17][18][19][20][21][22][23][24][25][26][27][28] These phosphorescent metal complexes often posses better photophysical properties than organic fluorophores, such as long luminescence lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…[17,21,22,39] However, a neutral Ir III complex functionalized with peptides for specific targeting of a cancer associated membrane receptor has not been reported yet. In this paper, we present CXCR4 targeting with three different Ac-TZ14011 peptide-conjugated Ir III complexes, Ir-(Ac-TZ14011) (8), Ir-(Ac-TZ14011) 2 (9) and Ir-(Ac-TZ14011) 3 (10).…”
Section: Introductionmentioning
confidence: 99%
“…[8] There have been a few reports of optical imaging probes designed to target CXCR4; most involved fluorescently tagged peptides with high binding affinities. [9][10][11] In 2007, Archibald et al reported a small molecule with structural similarities to AMD3100 that also contained a fluorescent rhodamine attachment. [12] Whilst the uncomplexed compound did not inhibit the binding of CXCR4-specific monoclonal antibodies, the corresponding copper complex was shown to have more favourable binding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we described fluorescence-based ligand screening assays as an alternative to radioisotope assays. 6,7) Protein kinase C (PKC) isozymes, which are classified as Ser/Thr kinases, play a critical role in cellular signaling pathways related to proliferation, 8,9) differentiation, 10) and apoptosis. 11,12) PKC has 11 isozymes which are classified into three subtypes: conventional PKC (cPKC; α, β I/II , γ), novel PKC (nPKC; δ, ε, η, τ) and atypical PKC (aPKC; ζ, λ, ι).…”
mentioning
confidence: 99%